TINJAUAN YURIDIS PERJANJIAN FINTECH DALAM KEABSAHAN PERJANJIAN TERHADAP JENIS PERJANJIAN - Prasetyanov, Yudha (Ensiklopedia of Journal, 2024)
Abstract: Fintech, or financial technology, falls under the category of unnamed agreements (innominate contracts). This is because agreements made in the context of fintech, such as loan agreements through peer-to-peer lending platforms or agreements for the use of digital payment services, are not specifically regulated in the Indonesian Civil Code (KUHPerdata) under a specific name. Although fintech is not specifically regulated, fintech agreements remain valid and binding as long as they meet the validity requirements of agreements stipulated in Article 1320 of KUHPerdata, namely: Agreement of the parties. Capacity to enter into a contract. A specific object. A lawful cause. This research is normative in nature, using a statute approach, a conceptual approach, and a comparative approach. Overall, fintech agreements must adhere to the basic principles of contract law as regulated in the Civil Code and other related regulations to ensure validity and legal protection for all parties involved.Keywords: fintech, binding, peer-to-peer lending.